Proceedings of the 3rd European Conference on Computer Network Defense - Siris, Vasilios; Anagnostakis, Kostas; Ioannidis, Sotiris; Trimintzios, Panagiotis; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
Proceedings of the 3rd European Conference on Computer Network Defense compiles revised and extended articles written by prominent researchers participating in the 3rd European Conference on Computer Network Defense (EC2ND). This volume presents information on intrusion detection and privacy protection. The text offers the latest information on advances in network security and serves as an excellent reference work for researchers and graduate students working in the area of computer network defense.
Tales from the Crypt: Fingerprinting Attacks on Encrypted Channels by Way of Retainting -- Towards High Assurance Networks of Virtual Machines -- Intrusion Detection Using Cost-Sensitive Classification -- A Novel Approach for Anomaly Detection over High-Speed Networks -- Elastic Block Ciphers in Practice: Constructions and Modes of Encryption -- Vulnerability Response Decision Assistance -- Alice, What Did You Do Last Time? Fighting Phishing Using Past Activity Tests -- QuiGon: The First Tool Against Clone Attack on Internet Relay Chat -- Defending Against Next Generation Through Network/Endpoint Collaboration and Interaction -- ISi-LANA - A Secure Basic Architecture for Networks Connected to the Internet.
Keywords: ENGINEERING; OPERATING SYSTEMS (COMPUTERS).; COMPUTER NETWORK ARCHITECTURES; COMPUTER COMMUNICATION NETWORKS; INFORMATION SYSTEMS; COMPUTER ENGINEERING; TELECOMMUNICATION; ENGINEERING; COMMUNICATIONS ENGINEERING, NETWORKS; MANAGEMENT OF COMPUTING AND INFORMATION SYSTEMS; COMPUTER COMMUNICATION NETWORKS; PERFORMANCE AND RELIABILITY; ELECTRICAL ENGINEERING; COMPUTER SYSTEMS ORGANIZATION AND COMMUNICATION NETWORKS